EKSEKUSI TERHADAP SAHAM YANG DIGADAIKAN BERKAITAN DENGAN BERAKHIRNYA JANGKA WAKTU GADAI DALAM SCRIPLESS TRADING SYSTEM - Krisna Permadi Budha, Ida Gede; Subha Karma Resen, Made Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015, 2015)
Scientific paper titled "Execution Against Shares pledged End of Period Relatingto Pawn In Scriptless Trading System", using normative research methods. Issues raisedis how to execute the pledged stock without paper relating to the expiration of the lien inscripless trading system. Based on the research conducted, the results showed that thepresence of the shares are at a third party, namely PT KSEI be mortgaged if bothparties agree. PT KSEI will do the freezing/blocking number of pledged securities in theSub Account on behalf of the collateral. The execution of the object lien pledge ofshares done by the rules that exist in the Civil Code under Article 1155 of the CivilCode is to parate and Article 1156 of the Civil Code executie is by private sale.
Keywords: Execution, Shares, Pledge, Scripless Trading